Counting the bodies: Estimating the numbers and spatial variation of Australian reptiles, birds and mammals killed by two invasive mesopredators. (15th March 2022) - Stobo‐Wilson, Alyson M.; Murphy, Brett P.; Legge, Sarah M.; Caceres‐Escobar, Hernan; Chapple, David G.; Crawford, Heather M.; Dawson, Stuart J.; Dickman, Chris R.; Doherty, Tim S.; Fleming, Patricia A.; Garnett, Stephen T.; Gentle, Matthew; et al.
Abstract: Aim: Introduced predators negatively impact biodiversity globally, with insular fauna often most severely affected. Here, we assess spatial variation in the number of terrestrial vertebrates (excluding amphibians) killed by two mammalian mesopredators introduced to Australia, the red fox ( Vulpes vulpes ) and feral cat ( Felis catus ). We aim to identify prey groups that suffer especially high rates of predation, and regions where losses to foxes and/or cats are most substantial. Location: Australia. Methods: We draw information on the spatial variation in tallies of reptiles, birds and mammals killed by cats in Australia from published studies. We derive tallies for fox predation by (i) modelling continental‐scale spatial variation in fox density, (ii) modelling spatial variation in the frequency of occurrence of prey groups in fox diet, (iii) analysing the number of prey individuals within dietary samples and (iv) discounting animals taken as carrion. We derive point estimates of the numbers of individuals killed annually by foxes and by cats and map spatial variation in these tallies. Results: Foxes kill more reptiles, birds and mammals (peaking at 1071 km −2 year −1 ) than cats (55 km −2 year −1 ) across most of the unmodified temperate and forested areas of mainland Australia, reflecting the generally higher density of foxes than cats in these environments. However, across most of the continent – mainly the arid central and tropical northern regions (and on most Australian islands) – cats kill more animals than foxes. We estimate that foxes and cats together kill 697 million reptiles annually in Australia, 510 million birds and 1435 million mammals. Main conclusions: This continental‐scale analysis demonstrates that predation by two introduced species takes a substantial and ongoing toll on Australian reptiles, birds and mammals. Continuing population declines and potential extinctions of some of these species threatens to further compound Australia's poor contemporary conservation record.